A profound density functional theory study to unravel the spectroscopic and molecular properties of two Flavanols differing in α‐pyrone ring position. Issue 4 (4th November 2019) - Hashmi, Muhammad Ali; Farooq, Umar; Bibi, Syeda Sidra; Naz, Sadia; Xu, Hong‐Guang; Asghar, Basim H.; Mabkhot, Yahia Nasser; Alsayari, Abdulrahman; Muhsinah, Abdullatif Bin; Khan, Ayesha
Abstract: A comprehensive theoretical model was designed for two new flavanols that have been reported from Glycosmis pentaphylla, differing in the placement of α ‐pyrone ring. The density functional theory (DFT) approach was utilized for computing different properties of these compounds to validate the experimental findings and stereochemical assignments. Electronic properties, geometric parameters, frontier molecular orbitals (FMOs), molecular electrostatic potential (MESP), and natural bond orbital analysis were performed for the first time at the PBE0‐D3BJ/def2‐TZVP level of theory for the compounds under study. The simulated vibrational frequencies for compounds 1 and 2 were computed and compared with the experimental results. nuclear magnetic resonance (NMR) ( 1 H and 13 C) chemical shift values were computed at the PBE0‐D3BJ/def2‐TZVP/SMDDMSO level of theory and showed a very good agreement with the experimental results for both the compounds. The electronic circular dichroism (ECD) and ultraviolet–visible (UV) spectra for both the compounds were obtained using time‐dependent DFT in methanol, whose results exhibited excellent correlation with experimental data. The intermolecular interaction effect on geometric parameters, vibrational frequencies, and electronic properties were studied for the first time. Abstract : A theoretical model was designed for two flavanols reported from Glycosmis pentaphylla, differing in the placement of the α ‐pyrone ring. Different properties of these compounds were computed to validate the experimental findings. Electronic properties, geometric parameters, frontier molecular orbitals, molecular electrostatic potential, NMR, UV, ECD, and natural bond orbital (NBO) analysis were performed at the PBE0‐D3BJ/def2‐TZVP level of theory for the compounds under study.